Elastic models of the glass transition applied to a liquid with density anomalies - Ciamarra, Massimo Pica (2015)
Elastic models of the glass transition relate the relaxation dynamics and the elastic properties of structural glasses. They are based on the assumption that the relaxation dynamics occurs through activated events in the energy landscape whose energy scale is set by the elasticity of the material. Here we investigate whether such elastic models describe the relaxation dynamics of systems of particles interacting via a purely repulsive harmonic potential, focusing on a volume fraction and temperature range that is characterized by entropy-driven water-like density anomalies. We do find clear correlations between relaxation time and diffusivity on the one hand, and plateau shear modulus and Debye–Waller factor on the other, thus supporting the validity of elastic models of the glass transition. However, we also show that the plateau shear modulus is not related to the features of the underlying energy landscape of the system, at variance with recent results for power-law potentials. This suggests that elastic models work even if the slow dynamics is not dominated by the potential energy landscape.